Pembelajaran Berbasis Proyek dan Dampaknya terhadap Hasil Belajar Siswa Pada Mata Pelajaran OTK Humas dan Keprotokolan - Winata, Hendri; Sonjaya, Nabila Putri (Universitas Pendidikan Indonesia (UPI), 2024)
In this research focused on the issue of low achievement of class To overcome this problem, this research aims to identify problems in the application of project-based learning methods (Project Based Learning) and their influence on the achievement of student learning outcomes.By using the pre-experiment method and quantitative approach, data was collected through treatment results by looking at the post-test results. There is documented data on learning outcomes in 2020/2021 and 2021/2022 which is data for comparing average scores to determine whether there are significant differences between the groups tested.The results of the analysis show that the application of project-based learning methods (Project based learning) has a positive and meaningful impact on the achievement of student learning outcomes, with a high level of correlation and a positive direction. Thus, it can be concluded that the use of project-based learning methods has a positive impact on student learning outcomes.